2018
DOI: 10.1136/bmjgh-2018-000970
|View full text |Cite
|
Sign up to set email alerts
|

Identifying health policy and systems research priorities on multisectoral collaboration for health in low-income and middle-income countries

Abstract: IntroductionWhile efforts to achieve Universal Health Coverage (UHC) and the Sustainable Development Goals (SDGs) have reinvigorated interest in multisectoral collaborations (MSCs) among the global health and development community, there remains a plethora of questions about how best to conceptualise, plan, implement, evaluate and sustain MSCs. The objective of this paper is to present research priorities on MSC for health from researchers and policymakers around the globe, with an emphasis on low-income and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 57 publications
0
57
0
3
Order By: Relevance
“…These gaps constrain the specificity of insights about MSCs, resulting in high-level recommendations that, while conceptually sound and intuitively appealing, leave many important questions unanswered (4).…”
Section: Aim 3: Methodological Gaps and Opportunities For Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…These gaps constrain the specificity of insights about MSCs, resulting in high-level recommendations that, while conceptually sound and intuitively appealing, leave many important questions unanswered (4).…”
Section: Aim 3: Methodological Gaps and Opportunities For Developmentmentioning
confidence: 99%
“…A paper by Glandon et al identifying health policy and systems research (HPSR) priorities on MSC for health in low and middle income countries (LMICs) demonstrated a clear need for more evidence on MSCs and a lack of clarity on the types of research designs and methods that can best generate that evidence (4). In this paper, we appraise the underlying research papers from the previously published HPSR priority-setting exercise to address our first two aims, namely to: 1) identify key research question domains ("meta questions") currently addressed in the MSC literature; and 2) describe research methods used to answer those questions (4). We also draw on participant input from a skill-building workshop at the Health Systems Research (HSR) Symposium in Liverpool, UK (8-12 October, 2018) to address our third aim: to identify methodological gaps and opportunities for MSC research, with a focus on LMICs.…”
Section: Introductionmentioning
confidence: 99%
“…É mencionada a carência de sistemas de monitoramento governamentais profícuos, que permitam a utilização de informações pertinentes como fonte de aprimoramento das ações propostas (Bennett et al, 2018;L. M. T. Garcia et al, 2014;Glandon, Meghani, Jessani, Qiu, & Bennett, 2018;Loewenson, 2013;Ndumbe-Eyoh & Moffatt, 2013;Sadana, Brown, Lee, Goldblatt, & Hosseinpoor, 2010).…”
Section: Contemplando a Relação Mencionada Foi Lançado Em 2007 O Prounclassified
“…A análise de políticas públicas usualmente remete à um processo cíclico dividido nas seguintes etapas sequenciais, mas interdependentes: formação de agenda; formulação de alternativas; tomada de decisão, implementação; avaliação (Frey, 1996;Howlett, Ramesh, & Perl, 2013;Secchi, 2010 (Glandon et al, 2018;Sadana et al, 2010).…”
Section: Ações Intersetoriais Para Saúde E O Desafio Do Monitoramentounclassified
See 1 more Smart Citation